Diagnostic Et Perspectives Du E-payment En Algérie - Benazzouz, Daouia; Mouterfi, Amel (جامعة الوادي - University of Eloued, 2022)
The electronic commerce in Algeria has experienced a significant evolution thanks to the rise of the Internet and the adoption of the law 18/05 (May 2, 2018) on its legalization,so the , electronic payment (epayment) - its main component - must follow this evolution . The objective of this study is to diagnose the effective use of e-payment in Algeria, since the launch of the first inter-bank transaction on October 04, 2016 to date, as well as its evolution, while trying to highlight the nature of the various brakes that slow down its development, and thus establish the conditions for success of the epayment system, by adopting a descriptive analytical approach of the data collected, fromthe actors concerned.
مقال
Keywords: E-payment ; commerce électronique ; diagnostic ; freins ; perspectives; E-payment, E-commerce, diagnosis, brakes, prospects.